SURFACE PLASMON RESONANCE ANALYSIS FOR BENZENE SENSING MEDIA USING SILVER AND Ta2O5 THIN FILMS - Mohamad, Haidar J.; Kafia, Shaymaa H.; Kadhum, Farah J. (Malaysian Journal of Science, 2024)
The increasing demand for optical sensors is driven by their wide applications, making surface plasmon resonance (SPR) play a crucial role in this field. In this study, a multilayered thin film consisting of tantalum pentoxide (Ta2O5) and silver (Ag) deposited on a glass prism was used to study SPR. The Ag layer thickness was fixed at 50 nm, while the Ta2O5 layer thickness varied from 0 to 70 nm. The Kretschmann configuration was employed to assess the sensitivity of air and gases with different refractive indices. Therefore, different layer thicknesses along with different wavelengths and angles were investigated. MATLAB software was employed to simulate and analyze SPR with a half-sphere prism to extend the incident angle. The simulation conditions with Fresnel equations were used to calculate the reflectivity and transmittance coefficients for the studied sample. The results revealed that the best output was at a Ta2O5 thickness of 50 nm to get optimal full width at half maximum of 2.4 and sensitivity factor of 162.5. This device works in the visible and infrared regions.